Clinico-functional features of myocardial infarction patients undergoing out-patient rehabilitation in the Polar North - Yu. A. Kornev (Российский кардиологический журнал)
Holter monitoring results were analyzed in 30 myocardial infarction patients undergoing out-patient rehabilitation. Myocardial ischemia episodes (MIE) were registered in 10 patients (33,3%). In 30% of cases, MIE were silent, associated with mild physical exertion, and low heart rate (HR) levels - 87,2+15,2 per minute. Arrhythmias were registered in all subjects (100%). Fifteen patients (50%) demonstrated high-class ventricular extrasystolia by Lown classification. Supraventricular tachycardia episodes were observed in 31% of cases. Spectral and temporal parameters of HR variability (HRV) were analyzed. Total variation power was reduced, especially in higher frequencies. Centralization index (CI) was increased in most participants (4,14+2,36 units). In 14 patients (46,6%), SDNN was lower than 100 ms. Parasympathic hypotonus was confirmed by declined rMSSD (22,5+8,55 ms) and pNN50% (4,36+3,66 ms). In 60% of cases, circadian index (CI) was reduced (1,19+0,07).